STUDENTS’ CRITICAL THINKING ABILITY IN INTEGRATED LEARNING MODEL - Putri Dwi Sundari; Parno Parno; Sentot Kusairi (Universitas Negeri Yogyakarta, 2018)
This study was aimed at analyzing the students’ critical thinking skills in the integrated 5E peer instruction learning cycle in temperature and heat material. This mixed-method research with embedded experimental design involved 33 students of class X in Sidoarjo state high school. The research instrument consists of treatment instruments and measurement instruments. The treatment instrument consists of syllabus, lesson plan, and student worksheet. The measurement instrument consisted of critical thinking skills tests, interview guide sheets and field notes. The test research instrument was in the form of 8 test questions developed based on critical thinking indicators proposed by Ennis with a reliability of 0.72. The quantitative data on students’ critical thinking skills were analyzed using paired t-test, while qualitative data were analyzed by reducing the results of student interviews. The results show that the students’ critical thinking skill in the temperature and heat materials increased after following the peer instruction integrated 5E learning cycle. The students have been able to build basic skills, provide simple explanations, organize strategies and tactics, make further explanations and are still unable to make conclusions from the physics problems presentedKEMAMPUAN BERPIKIR KRITIS SISWA DALAMMODEL PEMBELAJARAN TERINTEGRASIAbstrakPenelitian ini bertujuan menganalisis kemampuan berpikir kritis siswa pada model siklus belajar 5E terintegrasi peer instruction dalam materi suhu dan kalor. Penelitian mixed-method dengan desain embedded experimental ini melibatkan 33 siswa kelas X di SMA Negeri di Sidoarjo. Instrumen penelitian terdiri dari instrumen perlakuan dan instrumen pengukuran. Instrumen perlakuan terdiri dari silabus, RPP, dan LKS. Instrumen pengukuran terdiri dari tes kemampuan berpikir kritis, lembar panduan wawancara, dan lembar catatan lapangan. Instrumen penelitian tes berupa 8 soal uraian tes yang dikembangkan berdasarkan indikator berpikir kritis yang dikemukakan oleh Ennis dengan reliabilitas 0,72. Data kuantitatif kemampuan berpikir kritis siswa dianalisis menggunakan paired t-test. Data kualitatif dianalisis dengan melakukan reduksi terhadap hasil wawancara siswa. Hasil penelitian menunjukkan kemampuan berpikir kritis siswa pada materi suhu dan kalor meningkat setelah mengikuti pembelajaran siklus belajar 5E terintegrasi peer instruction. Siswa sudah mampu dalam membangun keterampilan dasar, memberikan penjelasan sederhana, mengatur strategi dan taktik, membuat penjelasan lebih lanjut, dan masih kurang mampu dalam membuat kesimpulan dari permasalahan fisika yang disajikan.